2020
DOI: 10.1111/jnc.15177
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Meis1, a transcriptional regulator, in mice and worms: Neurochemical and behavioral characterizations with implications in the restless legs syndrome

Abstract: Restless legs syndrome is a sleep-related sensorimotor neurological disease affecting up to 10% of the population. Genetic analyses have identified Myeloid Ecotropic viral Integration Site 1 (MEIS1), a transcriptional regulator, to be associated with not only the restless legs syndrome but also self-reported symptoms of insomnia and sleep. This study is to determine if Meis1 deficiency in mice can lead to restless legs syndrome-like phenotypes, and if it is the case, what the underlying mechanisms are. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Finally, the number of ChAT + cholinergic interneurones, an important modulator of MSNs, was not altered in the Meis1 +/− striatum. This observation is in agreement with a recent report of normal content of these interneurones in a distinct model of Meis1 deficiency (Lyu et al., 2020). However, Lyu et al reported that Meis1 deficiency affected synchronous firing of these cells, which remains to be evaluated in the models we investigated here.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Finally, the number of ChAT + cholinergic interneurones, an important modulator of MSNs, was not altered in the Meis1 +/− striatum. This observation is in agreement with a recent report of normal content of these interneurones in a distinct model of Meis1 deficiency (Lyu et al., 2020). However, Lyu et al reported that Meis1 deficiency affected synchronous firing of these cells, which remains to be evaluated in the models we investigated here.…”
Section: Discussionsupporting
confidence: 94%
“…A recent study by Lyu et al reported hyperac-tivity of Meis1-deficient mice resulting from deletion of the eighth exon of the Meis1 gene. This mouse model displayed decreased tyrosine hydroxylase protein expression associated with an increased dopaminergic turnover supporting abnormal signalling of dopaminergic neurones projecting to the striatum, although without any apparent changes in striatal DRD2 protein expression (Lyu et al, 2020).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Genome-wide association studies have linked polymorphism of MEIS1 to an increased risk of "Restless legs syndrome" [11][12][13][14]. MEIS1 has also been linked to insomnia and sleep disorders [15][16][17]; in addition, it appears to be an essential regulator of the cardiomyocytes cell cycle [18][19][20].…”
Section: Introductionmentioning
confidence: 99%